Fluorescent homooxacalixarenes: recent applications in supramolecular systems - Marcos, Paula M.; Berberan-Santos, Mário N. (Frontiers in Chemistry, 2023)
This review covers recent advances (from 2006 to date) in supramolecular systems based on fluorescent homooxacalixarenes, namely hexahomotrioxacalix[3]arenes, dihomooxacalix[4]arenes and tetrahomodioxacalix[4]arenes, focusing on fluorescence sensing using their intrinsic fluorescence (built-in mesitol-like groups) or the extrinsic fluorescence of organic fluorophores, either covalently linked to the calixarenes or forming supramolecular complexes with them. Sensing applications of ions, ion pairs and neutral molecules are discussed, as well as the potential measurement of temperature based on thermally activated delayed fluorescence.